Tubuh dan Relasi Gender: Wacana Pascakolonial Dalam Novel “The Scarlet Letter” Karya Nathaniel Hawthorne - M. Yuseano Kardiansyah (POETIKA, 2017)
This research analyzes postcolonial discourse about body and gender relation in Nathaniel Hawthorne’s The Scarlet Letter that tells about obsession toward morality, gender oppression, punishment for sinner, guilty feeling dan individual sin confession. The objective of this research is to reveal the resistance sides toward colonial construction that still exist in society’s social order and norm reflected in that novel. By applying postcolonialism approach and deconstruction method, it is proven that The Scarlet Letter depicts colonized (women) resistance behind its attitude and practice that seems submissive to the power of colonizer (society dan men’s domination).Key Words: Postcolonial Discourse, Body, Gender Relation, Deconstruction, Colonial Construction